Change Readiness On The Covid-19 Pandemic In Higher Education Activities: The Student Perspective - Nurillah Jamil Achmawati Novel; Rani Sukmadewi; Jovanscha Qisty Adinda Fildzah (Aliansi, 2022)
The COVID-19 pandemic has had both positive and negative impacts on various aspects of life, including the world of education. Social restrictions cause teaching and learning activities to be carried out from their respective workspaces, or what is known as online learning. This study identifies the changing readiness of students in higher education related to the adaptation of online learning activities. As the result of all the dimensions specified, only two dimensions are optimal, namely "adaptability" and "tolerance for ambiguity." Meanwhile, the dimensions of resourcefulness, optimism, confidence, adventurousness, and passion/drive are still not optimal. As the conclusion, that the change readiness in online learning still needs attention to be improved. Pandemi covid-19 telah menimbulkan dampak positif dan negatif pada berbagai aspek kehidupan, tak terkecuali pada dunia pendidikan. Pembatasan sosial menyebabkan aktivitas belajar mengajar harus dilaksanakan dari ruang kerja masing-masing, atau disebut dengan pembelajaran secara daring-dalam jaringan (online). Penelitian ini mengidentifikasi kesiapan berubah para mahasiswa di Perguruan Tinggi terkait dengan adaptasi aktivitas pembelajaran secara online. Hasilnya dari seluruh dimensi yang diidentifikasi, hanya dua dimensi yang optimal yaitu “adaptability” dan “tolerance for ambiguity”. Sedangkan dimensi resourcefulness, optimism, confidence, adventurousness, dan passion/drive masih belum optimal. Secara keseluruhan dapat dinyatakan bahwa tingkat kesiapan berubah dalam pembelajaran online masih perlu perhatian untuk ditingkatkan.